Penyelesaian Sengketa Tanah Rumah Pribadi Perspektif Wahbah Az-Zuhaili - Tengku Khulafa Rasidin; Tetty Marlina Tarigan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the resolution of private residential land disputes from the perspective of Wahbah Az-Zuhaili. Land disputes often arise due to unclear ownership documents, conflicts among heirs, or boundary violations. This research employs a qualitative method with a case study approach to explore the background of disputes, resolution processes, and the application of Islamic legal principles according to Wahbah Az-Zuhaili. Data were collected through interviews, observations, and documentation from relevant parties. The findings indicate that land dispute resolution in this area is primarily conducted through family mediation and customary institutions, emphasizing principles of justice, deliberation, and avoiding prolonged conflicts. From Wahbah Az-Zuhaili's perspective, this approach aligns with maqashid sharia, aiming to safeguard property rights, minimize harm, and maintain social harmony. This study recommends strengthening Islamic legal literacy and land ownership awareness among the community to prevent future disputes.